Historical knowledge-genre as it relates to the reunification of Cameroon in selected Anglophone Cameroonian History textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Since the 1961 reunification of French and British Southern Cameroons, discourses of marginalisation, assimilation, “francophonisation”, “frenchification” and internal colonisation have emerged in public and academic circles to describe the plight of the minority Anglophone population of Cameroon in the reunified country. An important element of this plight has been the systematic abrogation of the federal constitution that was adopted as basis for the reunification. The calls therefore from the Anglophone populations have mostly revolved around two options: Either a return to federal form of government which was the basis for reunification or the establishment of an autonomous state for Southern Cameroons. Against this backdrop of Anglophone plight linked to reunification, this study sought to analyse Anglophone Cameroonian History textbooks with regards to their application of historical genres and knowledge as it relates to the reunification of Cameroon. The study adopted a qualitative approach using an interpretivist paradigmatic lens. The methodology employed was qualitative content analysis of three purposively selected Anglophone Cameroon History textbooks. The findings revealed that the textbooks employ explanatory, narrative and descriptive historical genres. These genres were all characterised by factorial and consequential explanations of actions of elite historical characters, selected historical events, and places. Furthermore, it was realised that the textbooks made use of a highly overt substantive form of historical knowledge in the explanation of reunification – a form of historical knowledge indicative of rote learning. Lastly, there was an evident discourse of an Anglophone identity or nationalism in the textbooks by function of the historical genre and knowledge types exposed.
Keywords: Anglophone; Cameroon; Historical genre; Historical knowledge; Reunification; Textbooks